ILC2s regulate adaptive Th2 cell functions via PD-L1 checkpoint control - Schwartz, Christian (J Exp Med, 2017)
Group 2 innate lymphoid cells (ILC2s) are important effector cells driving the initiation of type 2 immune responses leading to adaptive T helper 2 (Th2) immunity. Here we show that ILC2s dynamically express the checkpoint inhibitor molecule PD-L1 during type 2 pulmonary responses. Surprisingly, PD-L1:PD-1 interaction between ILC2s and CD4(+) T cells did not inhibit the T cell response, but PD-L1–expressing ILC2s stimulated increased expression of GATA3 and production of IL-13 by Th2 cells both in vitro and in vivo. Conditional deletion of PD-L1 on ILC2s impaired early Th2 polarization and cytokine production, leading to delayed worm expulsion during infection with the gastrointestinal helminth Nippostrongylus brasiliensis. Our results identify a novel PD-L1–controlled mechanism for type 2 polarization, with ILC2s mediating an innate checkpoint to control adaptive T helper responses, which has important implications for the treatment of type 2 inflammation.